2020
DOI: 10.1021/acsaelm.0c00777
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Power Factors in Ultrawide-Band-Gap GaB3N4 and AlB3N4 for High-Temperature Thermoelectric Applications

Abstract: With recent thermoelectric studies concentrating too much on low- and mid-temperature applications, an interesting question is, “are there any materials suitable for high-temperature thermoelectric operations?” To answer this, we have demonstrated in this work the viability of the ternary ultrawide-band-gap materials GaB3N4 and AlB3N4 for high-temperature thermoelectric applications using the first-principles calculation method. Our accurate transport calculations, considering both elastic and inelastic scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Figure b plots the calculated m * and E def of the as-sintered samples. It is noted that we do not use the second-order partial derivative of CBM to calculate the m * as commonly used in other thermoelectric materials due to the linear band dispersion of CBM in Ag 2 Se-based materials. As can be seen, m * of ternary Ag 2 Se 1– x Te x decreases with increasing x, which is the reason for the decrease in S .…”
Section: Resultsmentioning
confidence: 84%
“…Figure b plots the calculated m * and E def of the as-sintered samples. It is noted that we do not use the second-order partial derivative of CBM to calculate the m * as commonly used in other thermoelectric materials due to the linear band dispersion of CBM in Ag 2 Se-based materials. As can be seen, m * of ternary Ag 2 Se 1– x Te x decreases with increasing x, which is the reason for the decrease in S .…”
Section: Resultsmentioning
confidence: 84%
“…Recent reports indicated that the AMSET package generates better results compared to the BoltzTrap code. [28][29][30] Therefore, we use AMSET to calculate the electronic transport properties in this work. The calculations of the input parameters are calculated in a dense mesh of 10 Â 10 Â 10, according to the convergence test as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%